Development of a mesoporous silica based solid‐phase extraction and ultra‐performance liquid chromatography–MS/MS method for quantifying lignans in Justicia procumbens. Issue 5 (9th March 2020) - Shen, Qing; Wang, Honghai; Li, Shiyan; Feng, Junli; Song, Gongshuai; Zhang, Yiqi; Ma, Jianfeng; Wang, Haixing
Abstract: Justicia procumbens is a food and medicine homologous variety, popularly used for making vegetable soups. In this study, a novel mesoporous silica was synthesized and used as the sorbent of SPE for the purification of lignans from J. procumbens . A laboratory‐made SPE cartridge was packed with 100 mg of mesoporous silica, which was washed with 10% methanol and eluted using 0.8 mL acetonitrile after sample loading. Afterward, the extract was analyzed by ultra‐performance liquid chromatography (UPLC) and MS/MS. All the lignans were efficiently separated in 6 min with the noise level in the range of 50–150 cps. 6′‐Hydroxy justicidin B, 6′‐hydroxy justicidin A, justicidin B, chinensinaphthol methyl ether, justicidin C, and neojusticdin A were identified to be the dominant molecular species in J. procumbens with contents of 0.065−0.37 mg/g in three tested sample batches from different geographic origins. In conclusion, the proposed mesoporous silica based SPE UPLC–MS/MS method is efficient in linearity ( R 2 = 0.9989−0.9996), sensitivity (LOD ≤0.13 μg/kg and LOQ ≤0.42 μg/kg), precision (RSDintra‐day ≤3.12 and RSDinter‐day ≤4.56), and recovery (83.42−96.11%, RSD ≤2.88%).